2022
DOI: 10.1093/eurheartj/ehac572
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous physical activity, incident heart disease, and cancer: how little is enough?

Abstract: Aims Vigorous physical activity (VPA) is a time-efficient way to achieve recommended physical activity levels. There is a very limited understanding of the minimal and optimal amounts of vigorous physical activity in relation to mortality and disease incidence. Methods and results A prospective study in 71 893 adults [median age (IQR): 62.5 years (55.3, 67.7); 55.9% female] from the UK Biobank cohort with wrist-worn accelerom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 49 publications
7
61
0
1
Order By: Relevance
“…In contrast to questionnaires, wearable devices such as wrist 24,25 or thigh 26,27 accelerometers continuously record movement at a high resolution allowing them to capture fine-grain patterns of brief physical activity bouts, such as VILPA 19 . The rapidly growing use of wearable devices in research 25,[27][28][29][30] and among consumers 31 offers opportunities to better understand the health-enhancing potential of VILPA and analogous unexplored movement 'micro-patterns'. Such potential is greatly enhanced by the recent application of machine learning [32][33][34] in studies using wearable devices to understand the health effects of movement.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to questionnaires, wearable devices such as wrist 24,25 or thigh 26,27 accelerometers continuously record movement at a high resolution allowing them to capture fine-grain patterns of brief physical activity bouts, such as VILPA 19 . The rapidly growing use of wearable devices in research 25,[27][28][29][30] and among consumers 31 offers opportunities to better understand the health-enhancing potential of VILPA and analogous unexplored movement 'micro-patterns'. Such potential is greatly enhanced by the recent application of machine learning [32][33][34] in studies using wearable devices to understand the health effects of movement.…”
Section: Articlementioning
confidence: 99%
“…As the length of raw bouts within these two VILPA frequency exposures was highly variable, we length-standardized analytic bouts to one minute (for raw bouts lasting up to 1 minute) or two minutes (for raw bouts lasting up to 2 minutes) using a rolling sum on the time-series data until 1 or 2 minutes, respectively, was reached or exceeded. For example, a participant with five consecutive raw bouts lasting up to 1 minute each (20,30,20,40, and 10 seconds long), would be assigned 1.83 analytic bouts: the first three raw bouts would count as one and the rolling sum would be reset; then the last two raw counts would count as 0.83 length-standardised bouts (50 seconds divided by 60). This bout handling has analytic and interpretational advantages: a) it mitigates against the problem of multicollinearity between raw VILPA frequency and daily VILPA duration, and b) permits a more concrete behavioural interpretation of the VILPA frequency findings than raw bouts, as each length-standardised bout can be specifically interpreted as lasting 1 minute or 2 minutes.…”
Section: Definition Of Vilpa and Choice Of Bout Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that PA is always beneficial, even if done for a few minutes but on a regular basis [ 53 ]. Together with this point, recent reports state that at least 20 min per day of moderate to intense PA for 5 days per week can lead to a 16 to 40% reduction in the risk of suffering cardiovascular diseases among adults [ 54 ]. This amount of time is similar to the figure studied in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that vigorous and moderate PA have been extensively studied for their social and health bene ts (Thompson 1996;Wannamethee and Shaper 2001;Rennie et al 2003b, a;Richardson et al 2013;Valero-Elizondo et al 2016;Liu et al 2020;Ahmadi et al 2022), the evidence regarding their effects is mixed. Additionally, while research in developed countries has suggested a link between occupation-related PA trends and chronic health issues like obesity, the impact of levels of PA on health in developing countries is not clear.…”
Section: Association Between Levels Of Physical Activity and Chronic ...mentioning
confidence: 99%